(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Modern democratic countries have several obstacles, one of the most important being the effective management of ethnocultural plurality. The kinds of ethnocultural groups present in any given country determine the extent and nature of the ethnocultural plurality inside. That is one way in which they are also multicultural. Not only has immigration been a problem for multiculturalism, but so has the question of how to control ethnocultural pluralism, which arises from the fact that many countries have historically and geographically concentrated populations of people who identify as national minorities. Many Western cultures are worried about social cohesiveness due to the rising ethnic variety. People are worried that as communities become more diverse, social bonds weaken because people no longer share the same beliefs and behaviours. One possible outcome is a decline in public support for the welfare state, an increase in criminal activity, xenophobia, parallel societies, and political and religious fanaticism.